Synthesis and Characterization of Azo-based Compounds as Energy Storage Materials - Yadav, Pramod Kumar (International Journal of Applied Sciences and Biotechnology, 2023)
Two redox active azo-based materials have been synthesized and characterized by elemental analysis (C, H, N), IR, NMR (1H & 13C) and single crystal X-ray diffraction analysis. Both the azo-based materials, the ligand 1 and its MOF 2 exhibit good electrochemical performances but the capacity of MOF 2 is higher than the ligand 1. Int. J. Appl. Sci. Biotechnol. Vol 11(4): 217-221.